Effects of viscous dissipation and heat source on unsteady MHD flow over a stretching sheet - Machireddy Gnaneswara Reddy; Polarapu Padma; Bandari Shankar (Ain Shams Engineering Journal, 2015)
The aim of this paper is to present the unsteady magnetohydrodynamic (MHD) boundary layer flow and heat transfer of a fluid over a stretching sheet in the presence of viscous dissipation and heat source. Utilizing a similarity variable, the governing nonlinear partial differential equations are first transformed into ordinary differential equations before they are solved numerically by applying Keller Box method. Effects of physical parameters on the dimensionless velocity and temperature profiles were depicted graphically and analyzed in detail. The numerical predictions have been compared with already published papers and good agreement is obtained. Finally, numerical values of physical quantities such as the skin friction coefficient and the local Nusselt number are presented in tabular form. Heat transfer rate at the surface increases with increasing values of Prandtl number and unsteadiness parameter whereas it decreases with magnetic parameter, radiation parameter, Eckert number and heat source parameter.